2020
DOI: 10.3389/fonc.2020.00321
|View full text |Cite
|
Sign up to set email alerts
|

The Landscape of Somatic Copy Number Alterations in Head and Neck Squamous Cell Carcinoma

Abstract: Head and neck squamous cell carcinoma (HNSCC) is the sixth most common malignancy worldwide. Somatic copy number alterations (CNAs) play a significant role in the development of this lethal cancer. In this study, we present a meta-analysis of CNAs for a total of 1,395 HNSCC samples. Publicly available R packages and in-house scripts were used for genomic array data processing, including normalization, segmentation and CNA calling. We detected 125 regions of significant gains or losses using GISTIC algorithm an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 75 publications
3
20
0
Order By: Relevance
“…Likewise, in HNSCC, 11q loss is associated with cell line resistance to radiation and is linked to poor outcome in oral cavity cancer 30,41 . Several studies have highlighted the higher prevalence of 11q loss in HPV+ HNSCC as opposed to HPV− tumors, 37,42 and distal 11q loss is robustly associated with HPV‐driven carcinomas of the uterine cervix 43 . To our knowledge, no prior studies have demonstrated an association between distal 11q loss and VAF heterogeneity or CNV burden, as we herein report in HPV+ OPSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in HNSCC, 11q loss is associated with cell line resistance to radiation and is linked to poor outcome in oral cavity cancer 30,41 . Several studies have highlighted the higher prevalence of 11q loss in HPV+ HNSCC as opposed to HPV− tumors, 37,42 and distal 11q loss is robustly associated with HPV‐driven carcinomas of the uterine cervix 43 . To our knowledge, no prior studies have demonstrated an association between distal 11q loss and VAF heterogeneity or CNV burden, as we herein report in HPV+ OPSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mesenchymal cells such as fibroblastic reticulum cells (CK-positive interstitial reticulum cells, CIRCs) can also express KRT18 in reactive LNs [30] and occur in large numbers in tumor-draining LNs that are subcapsular in the paracortical regions [31,32]. However, 11 of the 14 LN-DTCs displayed typical HNSCC copy number alterations similar to BM-DTCs [33]. In addition, we saw in the five patients with available material from both compartments that the LN-DTCs sometimes cluster very closely with the BM-DTCs of the same patient.…”
Section: Discussionmentioning
confidence: 99%
“…The Genomic Identification of Significant Targets in Cancer (GISTIC2.0) algorithm was utilized to classify the copy number variant genes with remarkable gains and losses ( Mermel et al, 2011 ). The confidence level was set to 0.95, and other parameters were left at default settings ( Luo et al, 2020 ; Yang et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%